Relationship between Varicocele and Male Hypogonadism: A Review with Meta-Analysis - Giorgio Ivan Russo; Maria Giovanna Asmundo; Sarah Perelli; Rosita A. Condorelli; Aldo E. Calogero; Rossella Cannarella; Sandro La Vignera (Endocrines, 2022)
The relationship between varicocele and hypogonadism becomes clearer everyday thanks to the most recent literature, particularly with regards to the impact of varicocele repair on serum testosterone level improvement in hypogonadal patients. We selected English articles published from 1964 to September 2021. The search terms “varicocele” and “hypogonadism” were used as filters. A total of 102 studies have been obtained. For the meta-analysis, the pooled mean differences (MDs) for continuous variables and the ln(OR) were used for data pooling observational studies. A total of 15 articles have been finally included: nine retrospective and six observational. Testosterone levels pre- and after surgery were reported in four studies. There was statistically significant heterogeneity in these studies (chi2 = 267.09, I2 = 72%; p = 0.01). Mean differences of total testosterone was statistically different in men pre- and after-surgery (mean difference = 106.76; p < 0.0001). It is indeed established that altered environments caused by varicocele cause pantesticular insult, but it has not been unequivocally determined whether men with varicocele are at increased risk for the development of clinical hypogonadal symptoms.